Base-Catalyzed Intramolecular Defluorination/O-Arylation Reaction for the Synthesis of 3-Fluoro-1,4-oxathiine 4,4-Dioxide - Kang, Lei; Zhang, Jinlong; Yang, Huameng; Qian, Jinlong; Jiang, Gaoxi (Synlett, 2021)
A novel process involving base-catalyzed intramolecular defluorination/O-arylation of readily available α-fluoro-β-one-sulfones was realized and provided a series of 3-fluoro-1,4-oxathiine 4,4-dioxide derivatives in good to excellent yields. Unlike traditional defluorination reactions with stoichiometric base as the deacid reagent, this process is triggered by a catalytic amount of base (TMG: tetramethylguanidine) and molecular sieves serve as both an adsorbent to remove HF acid and an activator to assist C–F bond cleavage.
Keywords: base catalysis; defluorination; O-arylation; metal-free reactions; 1,4-oxathiines